Prevalence and Risk Factors of Third-and Fourth-degree Perineal Tears During Vaginal Delivery Among Women in Qom, Iran - Zohre Khalajinia; Mohammad Hassan Sharifi; Roghayyeh Ahangari; Fatemeh Sadat Mousavi; Mostafa Vahedian (Journal of Holistic Nursing and Midwifery)
Introduction: Third- and fourth-degree perineal tears are considered severe, whose prevalence rate is different based on the population, place, and time, and several factors can be involved in their occurrence. Objective: This study aims to determine the prevalence of severe perineal tears during normal vaginal delivery (NVD) and its risk factors among women in Qom, Iran. Materials and Methods: This is a descriptive-analytical retrospective study with a case-control design, which was conducted on the medical records of women who gave birth from March 2010 to March 2019 in three teaching hospitals in Qom (n=115,107). Those with third- and fourth-degree perineal tears were put in the case group (n=138), and those with no severe perineal tears were considered as controls (n=138). Information was collected using a checklist surveying demographic information, previous medical history, and obstetric information. The data analysis was done using independent t-test, chi-square test, Fisher’s exact test, and multivariate logistic regression analysis. The significance level was set at 0.05. Results: Among 115,107 childbirths in the hospitals, 138 cases (0.12%) had third- and fourth-degree tears. The mean age of women was 27.00±4.64 years and their mean gestational age was 39.09±1.05 weeks. None of the mothers consumed alcohol, and only two were smokers. The birth weight of newborns, parity, length of the first and second stages of labor, nationality, and time of delivery were significantly different between the two groups (P<0.05). The results of the multivariate logistic regression analysis showed that only the variables of birth weight of newborn (OR=0.91, 95% CI; 0.96%-0.99%, P=0.009), length of the first stage of labor (OR=0.06, 95% CI; 0.02%-0.19%, P=0.001) and length of the second stage of labor (OR=0.04, 95% CI; 0.03%-1.1%, P=0.001) were the significant predictors of severe perineal tears. Conclusion: the high birth weight of newborns and the prolongation of the first and second stages of labor are the risk factors for severe perineal tears. Therefore, it is recommended that obstetricians in Iran pay attention to these risk factors in the management of the labor process.